Nonprofit Planning and Impact with Regard to the 2018 Tax Law - Rebecca Padot (Journal of Public and Nonprofit Affairs, 2023)
The Tax Cuts and Jobs Act (TCJA) is considered the largest tax overhaul since 1986 and was anticipated to produce declining charitable donations for nonprofits and was expected to create disruption across the nonprofit sector in 2018. This study tests whether small nonprofits (under $250,000 in revenues) or large nonprofits (over $250,000 in revenues) planned differently due to the law and secondly, how they were affected by the law. Utilizing survey data from 50 nonprofits, this research offers qualitative data on both large and small nonprofit organizational awareness as it relates to the rollout of the law.